PENGARUH GIZI KURANG TERHADAP PENCAPAIAN PERKEMBANGAN ASPEK MOTORIK KASAR DAN MOTORIK HALUS PADA ANAK USIA 0-36 BULAN DI WILAYAH PUSKESMAS JATI KUDUS - Rusnoto Rusnoto; Noor Cholifah (Jurnal Ilmu Keperawatan dan Kebidanan, 2014)
Malnutrisi is circumstance patologis of arising out of effect of is lack of asupan energi protein and  during  a  given  time  period.  If  child  experience of  less  gizi,  clear  hence  will  be  dangerous  to continuity of child life , its problem is child stand in need of kecukupaan gizi to process growth and growth  which  exactly  take  place  fast  very  in  age  batita.  growth  And  growth  represent  health  gizi parameter  which sensitive  enough to assess child health, especially the and batita baby child. This research aim to to know influence  malnutrisi to harsh  growth motorik attainment time accuracy and refine at age child 0-36 month;moon in Puskesmas Jati Kudus.Intake sampel Method in the non random sampling , old fellow bringing his child to posyandu (  specially  the  age  child  0-36  month;moon)  in  Puskesmas  Jati  Kudus  as  sampel  in  this  research. Mount  malnutrisi  measured by using criteria  WHO-NCHS and  mount child  growth attainment time accuracy [in] measure by using kuisioner ( DDST) and KPSP. Research Location [in] Puskesmas Jati Kudus From result of enumeration indicate that value of X calculate 10,97 and assess X table 10,645 [at]  harsh  motorik  and  smooth  motorik, hence  interpretasinya  is  there  influence  of  malnutrisi  to accuracy of time attainment of  harsh  motorik [at] child of age 0-36 month;moon in Puskesmas Jati Kudus.Conclusion from this research expected by energy of health can improve of about gizi of his influence  and child to  growth and  growth especially child of baby and batita. For  the researcher is hereinafter expected more complete relevant research with this research, so that get better result.